The Effect of Wood Knot as a Defect on Modulus of Elasticity (MOE) and Damping Correlation - Mohammad Ali HOSSEIN; Mahdi SHAHVERDI; Mehran ROOHNIA (Notulae Scientia Biologicae, 2011)
This research was carried out to investigate the influence of knots on modulus of elasticity and on damping factor of vibration. Rectangular bars from Cupressus arizonica wood were used. Five individual trees were selected, and samples of 2*2*36 cm were cut and conditioned at 21C and 65% relative humidity. Experiments based on free vibration and free-free bar method were performed and controlled in static bending test due to their modulus of elasticity. As expected, this kind of defect showed significant effects on modulus of elasticity, damping factor of vibration and FFT diagrams. A significant relation was observed between modulus of elasticity and damping factor between the two dynamic and static methods, but this relation decrease about 60% in knot-containing specimens. Modes of FFT spectrums of defect-free specimens were pick-like, symmetric specimens without any breaks, but the spectra of knot-containing samples spectrums were entirely asymmetric. Applying these diagrams in order to recognize the suitability or unsuitability of a piece of wood for specific applications, especially due to internal defects that are not visible, could be very important, and must be considered in future research.